A Post-Keynesian approach as an alternative to neoclassical in the explanation of monetary and financial system - Savvas Zachariadis (Financial Studies, 2020)
The aim of this paper is to provide a Post-Keynesian view to economic theory as an alternative to traditional theory. Keynesian economics consists of an approach to economics derived mainly from the work of Keynes. It is grounded on the fields of observations of stylized facts of the economy and attempts to provide solutions to arising problems, which cannot be adequately explained and resolved by mainstream theory. We wish not in this paper to contradict the conventional with Keynesian and Post-Keynesian theory, but instead to provide an alternative and complementary view. However, we highlight the differences between traditional neoclassical theory and Post-Keynesian macroeconomics. Therefore, we shall focus on Post-Keynesian analysis on the operation of monetary and financial system in the endeavourto fill gaps on the explanation of relative phenomena. The main scope is the explanation of the financial system and financial stability.
Keywords: B50; E44; E50; 330; Post-Keynesian; neoclassical theory; monetary policy; financialsystem; financial instability